The Virgin Mary in the Reign of Mary Tudor - Wizeman, William (Studies in church history, 2004)
Evidence of devotion to the Virgin Mary in the restored Catholic Church of the reign of Mary Tudor survives in numerous religious texts published from 1553 to 1558. These sermons, catechetical texts, primers, and books of devotion and polemic were written to aid the restoration of early modern Catholicism in England after twenty years of religious tumult. By considering how these texts treat devotion to Mary, it is possible to answer two questions. First, was the cult of the saints in Marian England, particularly that of the Virgin, ‘one of [t]he abiding casualties of the preceding reformations’, as Ronald Hutton has argued from the few gilds and pilgrimage centres restored during this period? Secondly, does devotion to the Virgin present any clues as to the nature of the Marian Church? Did it hark back to the Church of the 1520s? Did it embrace much evangelical belief and eschew much traditional religion, as Lucy Wooding argues in her recent monograph? Or was it akin to the Catholic Reformation in Europe? In order to answer these questions, it would be useful to begin by evaluating two texts that possessed semi-official status in the Marian Church, the use and frequent printing of which were encouraged by the likes of Cardinal Pole: Bishop Edmund Bonner of London’s catechetical work, A Profitable Doctryne, and the Wayland Primer, both printed in 1555.